Impact of Mobile Banking Usage Intensity On Idx-Listed Banks' Performance - Juanda, Kadek Yoga Ade; Kitri, Mandra Lazuardi (Integrasi Sains Media, 2024)
This study investigates the impact of mobile banking usage intensity on the performance of banks listed on the Indonesia Stock Exchange (IDX), specifically focusing on Return on Assets (ROA) and Return on Equity (ROE). The analysis is divided into pre-COVID-19 (2013-2019) and during/after COVID-19 (2020-2023). Data from 14 banks were examined using the Pooled Ordinary Least Squares (OLS) method. The results show that mobile banking usage positively affects bank performance in both periods. Prior to the pandemic, increased mobile banking transactions significantly enhanced profitability and equity returns, indicating improved efficiency in generating earnings from assets and a positive impact on returns to shareholders. This positive effect became more pronounced during and after the pandemic, reflecting a greater reliance on digital banking channels. The COVID-19 pandemic notably shifted consumer behaviour towards higher adoption of digital solutions. The study also highlights significant differences between small and large banks. For smaller banks, mobile banking usage did not significantly impact performance metrics, suggesting challenges in leveraging digital banking effectively. In contrast, larger banks experienced significant improvements in ROA and ROE due to mobile banking usage, benefiting from their substantial resources and advanced technological infrastructure. Overall, this research underscores the crucial role of digital transformation in enhancing bank performance, particularly during crises. The findings suggest that continued investment in mobile banking technologies is essential for sustaining and improving financial performance.